(untitled) (Economic and Political Thought, 2015)
The debt crisis revealed serious gaps in the hitherto economic management system of the European Union. First of all, the principles of the Stability and Growth Pact (SGP) turned out to be completely ineffective, since they did not prevent the European Union from getting into trouble as a result of irresponsible fiscal policy. Secondly, it became clear that the euro area had no instruments for management in a critical situation, which made it impossible to undertake relevant actions. In May 2010, the EU started to look for an answer to the question how to overcome the crisis. Special rescue funds were established to prevent the crisis from spreading all over Europe. In the article, the author analyses the quality of the EU decission (at the moment the decisison was taken) and the potential effectivness of the proposed aid system architecture.